Compositional engineering of metal-xanthate precursors toward (Bi1−xSbx)2S3 (0 ≤ x ≤ 0.05) films with enhanced room temperature thermoelectric performance. Issue 5 (11th January 2022) - Hu, Zhenyu; Deng, Longhui; Wu, Tingjun; Wang, Jing; Wu, Feiyan; Chen, Lie; Li, Qikai; Liu, Weishu; Lien, Shui-Yang; Gao, Peng
Abstract : Metal-xanthate precursors could achieve high quality (Bi1-x Sbx )2 S3 Films. Via manipulating phonon scattering and dislocation density, improved Seebeck coefficient and power factor can be achieved as −516.35 μ V K −1 and 170.10 μ W m −1 K −2, respectively. Abstract : The preparation of high-performance thermoelectric thin films can be challenging. Herein, we report the preparation, characterization, and thermoelectric performance of morphology-controlled bismuth sulfide (Bi2 S3 ) thin films using a single-source precursor, namely bismuth(iii ) ethylxanthate. Using this precursor, room-temperature thermoelectric thin-films could be prepared quickly and cost-effectively. We acquired the intrinsic Bi2 S3 thin films with electrical conductivity of 14.23 S cm −1 and Seebeck coefficient of −388.33 μV K −1 at room temperature, which are comparable to that of the bulk Bi2 S3 . Furthermore, a higher Seebeck coefficient could be achieved by adopting a composition engineering method to achieve an antimony (Sb)-doping solid solution, in which the phonon scattering and dislocation density could be manipulated. By tuning the mole fraction of Sb in the films, we further improved the Seebeck coefficient to −516.35 μV K −1 and the power factor to 170.10 μW m −1 K −2 with a solid solution of (Bi0.97 Sb0.03 )2 S3 . Thus, the chalcogenide composition engineering protocol can be a universal methodology to fabricate target semiconductors for thin-film thermoelectric applications, which may broaden the application of thermoelectric films in the field of microelectronic devices.